The Choice of Life in Plotinus’ Ennead III4 (15) - Tonelli, Malena (2025)
“The Choice of Life in Plotinus’ Ennead III4 (15)”. In Ennead III4 (15) Plotinus incorporates certain passages from Platonic dialogues that discuss the concept of the daimon. His analysis focuses on the soul–particularly the individual one–and how conduct should be understood. Although Porphyry gave this treatise the title On our allotted daimon, taken from the Phaedo, Plotinus’ starting point is rather the soul’s capacity, prior to its union with the body, to choose the daimon that will lead it to a particular type of life, as shown by the Myth of Er in the Republic. As can be seen, the responsibility lies in this choice and the body appears to play no role in shaping the conduct of the individual subject. An unintended consequence of this view is that the embodied soul, once the daimon has been chosen, would be unable to deteriorate or improve. Therefore, as I understand it, learning, the pursuit of virtue, and perhaps even the philosophical endeavor itself would become meaningless. In this paper I offer a close analysis of select passages from III4 (15) with the aim of examining the problem of the soul’s choice and decision-making, as well as its interaction with the body.